ANALYSIS ON ARTICLE 340 OF THE CRIMINAL CODE AND ARTICLE 388 OF THE CRIMINAL CODE IN THE JESSICA MIRNA CASE - Arifian Awang Budhiarta; Bardo Josua Schumacher Sitohang; Josephine Annabelle Djibu; Stevan Gabriel Louhenapessy (Problematika Hukum, 2022)
Murders in Indonesia vary widely. The definition of murder is a criminal act that results in the loss of a person's life. Currently, murders occur a lot in various regions in Indonesia. Apart from being influenced by motives, this is also a picture of the moral decline of this nation. It is so easy for someone to take another person's life, that the cause is worth investigating. The harshness of life and the fragility of religious education may also be factors in the ease with which someone can take another person's life. The crime of murder requires the role and duties of the authorities, namely the Police. Murder committed intentionally in its basic form is contained in Article 338 of the Criminal Code, the formulation of which is "Whoever intentionally takes the life of another person, is threatened with a maximum imprisonment of 15 years for murder." The crime of premeditated murder is also formulated in Article 340 of the Criminal Code, the formulation of which is "Anyone who deliberately and plans to kill another person is threatened with premeditated murder, with the death penalty or life imprisonment, or life imprisonment. Certain period, a maximum of twenty years.” In this case, the defendant Jessica Wongso was very depressed and in this trial, according to the author, there was no concrete and clear evidence because an autopsy was not carried out. Because, what is clear is that there must be an autopsy, not just a sampling of stomach organs. Therefore, this case feels very strange and there is no clarity or clear evidence at all. The family refused to carry out an autopsy because they were afraid it would cause damage to Mirna Salihin's body.Keywords: Murder; Premeditation; Autopsy; Laws